Link between light-triggered Mg-banding and chamber formation in the planktic foraminifera Neogloboquadrina dutertrei - Jennifer S. Fehrenbacher (Nature Portfolio, 2017)
The degree to which the diurnal light/dark cycle influences Mg-heterogeneity in foraminifera with complex shell morphologies remains unknown. Here, using highly spatially resolved analytical techniques, the authors investigate Mg-banding and calcification in isotope-labelledNeogloboquadrina dutertreispecimens.